EVALUATING THE IMPACT OF DIGITAL TRANSFORMATION ON PUBLIC SERVICE DELIVERY EFFICIENCY AND ACCOUNTABILITY - Zohaib Hassan Sain; Aulia Luqman Aziz; Uthman Shehu Lawal; Nurulannisa Abdullah; Shazadi Hina Sain (Acitya Wisesa: Journal of Multidisciplinary Research, 2025)
The digital revolution transforms public administration, notably service delivery efficiency and accountability. According to this study, the digital tools and platforms used by governments worldwide impact public service delivery efficiency and accountability. This study examines how digital technologies like e-governance and data analytics influence public sector operations and how organisational culture and leadership might offset these effects. A mixed-approaches design employing qualitative and quantitative methods achieved research aims. Semi-structured interviews and focus groups with public sector workers and others produced qualitative data, while surveys and secondary data analysis acquired quantitative data. Thematic analysis was done in NVivo for qualitative data, while descriptive statistics, correlation, and regression were done in SPSS for quantitative data. Quantitative analysis indicates that digital transformation strongly impacts service delivery efficiency (R² = 0.42, F (3, 246) = 15.67, p < 0.001) and accountability (R² = 0.36, F (3, 246) = 12.29, p < 0.001). Significant predictors of service delivery efficiency and accountability include digital transformation (β = 0.45, p < 0.001), organisational culture (β = 0.35, p < 0.01), and leadership (β = 0.32, p < 0.05). Qualitative studies revealed that automation, real-time data sharing, transparency, and public involvement improve efficiency and accountability. This research found that digital transformation boosts public administration efficiency and accountability. Implementation needs a supportive workplace and good leadership. This study argues that governments should encourage digital adoption, address data privacy concerns, and close the digital divide to provide inclusive and equitable digital services.